Measurements of the branching fractions of B+→pp[bar]K+ decays = Measurements of the branching fractions of B+→pp̄K+ decays - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (The European physical journal. C, Particles and fields, 2013)
The branching fractions of the decay $B^{+} → p \bar{p} K^{+}$for different intermediate states are measured using data, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb experiment. The total branching fraction, its charmless component $(M_{p\bar{p}}<2.85~\text {GeV}/c^{2})$and the branching fractions via the resonant $c\bar{c}$states ηc(1S) and ψ(2S) relative to the decay via a J/ψ intermediate state are Upper limits on the B+ branching fractions into the ηc(2S) meson and into the charmonium-like states X(3872) and X(3915) are also obtained.
Im Titel steht der zweite Buchstabe p mit einem Oberstrich
Im Titel ist "+" jeweils hochgestellt
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 585
Gesehen am 23.03.2021